2022
DOI: 10.2147/ndt.s347432
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Jingxin Zhidong Formula for Tic Disorders: A Randomized, Double Blind, Double Dummy, Parallel Controlled Trial

Abstract: Background:The Jingxin Zhidong formula (JXZDF), a traditional Chinese medicine, has been widely used to treat tic disorder (TD) in China. However, its efficacy has not yet been evaluated in a randomized controlled trial. We aimed to compare the effectiveness and safety of JXZDF and aripiprazole in patients with TD. Methods: In this randomized, double-blind, double-dummy, parallel controlled trial, 120 patients with TD, aged 6-16 years were randomly assigned to receive either JXZDF (n = 60, 17.6 g/day) or aripi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 15 , 16 SZR had also been used in a randomized, double blind, double dummy, parallel controlled trial with TS children. 17 Further studies could be designed to subsequent cell and animal experiments to reveal the underlying pharmacological and therapeutic effects of SZR for the treatment of TS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 15 , 16 SZR had also been used in a randomized, double blind, double dummy, parallel controlled trial with TS children. 17 Further studies could be designed to subsequent cell and animal experiments to reveal the underlying pharmacological and therapeutic effects of SZR for the treatment of TS.…”
Section: Discussionmentioning
confidence: 99%
“…32 SZR is a Chinese herbal medicine that has been widely used in sedatives and tranquilizers in traditional clinics. 17 Based on the current clinical and experimental research status of SZR treatment for TS, the present study further explored the mechanism of action of SZR by using a systems biology approach. In this study, SZR was found to have 10 compounds and 42 non-repeating targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fan et al [59] designed a randomized controlled trial to explore the clinical efficacy and safety of JXZDF in the treatment of TS. JXZDF is composed of the following drugs: Zhenzhumu (Concha Margaritifera), calcined Longgu (Os Draconis), Muli (Concha Ostreae), Suan zao ren (Semen Ziziphi Spinosae), Baiziren (Semen Platycladi), Baishao (Radix Paeoniae Alba), Jiangcan (Bombyx Batryticatus), Chaihu (Radix Bupleuri), www.md-journal.com Niubangzi (Fructus Arctii), Zhiqiao (Fructus Aurantii), Dilong (Lumbricus), Chantui (Periostracum Cicadae), and Baizhi (Angelica Dahurica).…”
Section: Tcm Treatment Practice Of Tsmentioning
confidence: 99%